Examining Temporal Structure of Speech with a Local Articulation Rate Metric - Jan Volín; Michaela Svatošová (Research in Language)
The primary goal of our study is to propose a method of calculating and visualising local articulation rate for research in temporal structure of speech. The method builds on proportional durations of vowels and consonants in Czech, which normalizes for inherent durations of phones. We first demonstrate the importance of temporal structure on several conspicuous features: phrase-final deceleration, prominence marking, parentheticals, and information structure constituents. We then describe our method stepwise so that it could be tested by interested parties. We illustrate such testing on a sample of news bulletin sentences produced by 26 speakers. The results confirm that our procedure can meaningfully reflect various temporal features, including the ‘information status’ of words in contextually grounded utterances.